Female genital mutilation and its effects among women of reproductive age in Kenya: Insights from Kenya Demographic and Health Survey 2022 - Jovinary Adam; Joyce Jebet (PLoS ONE, 2025)
Introduction Female genital mutilation (FGM) is a significant public health issue rooted in cultural traditions, affecting millions of women and girls. In Kenya, the practice is prevalent in various ethnic groups and is often associated with social and economic pressures. Objective To determine the prevalence of FGM, the factors associated with FGM, and its effects among women of reproductive age in Kenya. Methods This study used secondary data of a total 16,716 weighted women of reproductive age drawn from the 2022 Kenya Demographic and Health Survey. The study used the “svy” command in Stata to assign the sample weight. Multivariable logistic regression was used to assess significant factors associated FGM and statistical significance was set at a 5% significance level. Results The overall prevalence of FGM among women of reproductive age in Kenya was 14.8% (95% CI = 13.98, 15.67). The findings showed that the following factors were associated with FGM: age 30–39 years (aOR=1.66, 95% CI = 1.28, 2.16) and age 40–49 years (aOR=2.71, 95% CI = 2.06, 3.57), residing in rural areas (aOR=1.37, 95% CI = 1.11, 1.68), no education (aOR=3.45, 95% CI = 2.69, 4.41) or primary education (aOR=1.40, 95% CI = 1.20, 1.64), being poor (aOR=1.76, 95% CI = 1.38, 2.25) or middle-income (aOR=1.34, 95% CI = 1.08, 1.66), being married (aOR=1.71, 95% CI = 1.37, 2.13) or separated (aOR=1.56, 95% CI = 1.17, 2.07), believing that FGM is required by religion (aOR=2.03, 95% CI = 1.37, 2.99), culture (aOR=4.79, 95% CI = 3.80–6.05), and society (aOR=2.65, 95% CI = 1.96, 3.58), FGM continued to be practiced (aOR=2.76, 95% CI = 2.14, 3.55), having a male household head (aOR=1.19, 95% CI = 1.02, 1.38), and never listening to the radio (aOR=1.31, 95% CI = 1.11, 1.54). Additionally, the results indicated that the most common side effects were severe pain (70.3%) and heavy bleeding (45.9%). Conclusion FGM is still a prevalent practice in Kenya despite being outlawed. gender and social norms contribute to the sustenance of the practice. The emerging trends including medicalization and change in the age of cutting need to be addressed. The factors that accelerate and enhance the practice of FGM need to be addressed and advocate more against the practice of FGM as it is a violation of human rights.